(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Metabolic syndrome (MS) is a cluster of metabolic disorders, including obesity, insulin resistance, dyslipidemia, and arterial hypertension. It has been established that MS negatively affects the male reproductive system, leading to decreased testosterone levels, impaired spermatogenesis, and erectile dysfunction. This article examines the pathophysiological mechanisms underlying these disorders and discusses modern approaches to correcting reproductive dysfunction in men with MS.